PENGARUH TEKNIK TENDANGAN KAKI BAGIAN DALAM DAN BAGIAN LUAR TERHADAP KETEPATAN SHOOTING DALAM PERMAINAN FUTSAL PUTRI CLUB - Reza Fatchurahman; umi kalsum (IKIP PGRI KALIMANTAN TIMUR, 2025)
This study aimed to determine the relationship between arm muscle strength and angled serve ability in volleyball games of 10th grade students at State Senior High School 14 Berau in the 2024/2025 academic year. The sample size was 30, with a total sample size of 30. This study aimed to determine the effect of inside and outside kick techniques on shooting accuracy in the 2025 Internona Samarinda Women's Futsal Game. The method used in this study was a quantitative method with an experimental approach. The population was 42 students, with a total sample size of 42. Data collection techniques used were tests and measurements. The results of this study indicate a significant effect of inside-foot training on shooting accuracy in futsal at the Internona Samarinda Futsal Club in 2025, as evidenced by a calculated t value greater than the t value of 12.42 ˃ 2.02. Conversely, there was also a significant effect of outside-foot training on shooting accuracy in futsal at the Internona Samarinda Futsal Club in 2025, as indicated by a calculated t value greater than the t value of 23.14 ˃ 2.02. Coaches, teachers, and sports instructors, especially futsal players, are advised to use inside-foot and outside-foot kick training to improve their shooting ability on goal.